The Genome Project, Gnosticism and Personalism - Bedolla, Miguel (Studia Bioethica, 2011)
This article has four parts. The first is a brief description of the Human Genome Project and its possible connections to American Eugenics. The second part raises the question about the possibility that the Human Genome Project is a Gnostic project. The third part will state the fundamental notions of Personalism in contrast to Gnosticism. The fourth part is the conclusion and provides an example of the manner in which Personalism works in history.